HIV status disclosure to perinatally-infected adolescents in Zimbabwe: a qualitative study of adolescent and healthcare worker perspectives - Kidia, K; Mupambireyi, Z; Cluver, L; Ndhlovu, C; Borok, M; Ferrand, R (Public Library of Science, 2014)
INTRODUCTION and OBJECTIVES: Due to the scale up of antiretroviral therapy, increasing numbers of HIV-infected children are living into adolescence. As these children grow and surpass the immediate threat of death, the issue of informing them of their HIV status arises. This study aimed to understand how perinatally-infected adolescents learn about their HIV-status as well as to examine their preferences for the disclosure process. METHODS: In-depth interviews were conducted with 31 (14 male, 17 female) perinatally-infected adolescents aged 16-20 at an HIV clinic in Harare, Zimbabwe, and focused on adolescents' experiences of disclosure. In addition, 15 (1 male, 14 female) healthcare workers participated in two focus groups that were centred on healthcare workers' practices surrounding disclosure in the clinic. Purposive sampling was used to recruit participants. A coding frame was developed and major themes were extracted using grounded theory methods. RESULTS: Healthcare workers encouraged caregivers to initiate disclosure in the home environment. However, many adolescents preferred disclosure to take place in the presence of healthcare workers at the clinic because it gave them access to accurate information as well as an environment that made test results seem more credible. Adolescents learned more specific information about living with an HIV-positive status and the meaning of that status from shared experiences among peers at the clinic. CONCLUSIONS: HIV-status disclosure to adolescents is distinct from disclosure to younger children and requires tailored, age-appropriate guidelines. Disclosure to this age group in a healthcare setting may help overcome some of the barriers associated with caregivers disclosing in the home environment and make the HIV status seem more credible to an adolescent. The study also highlights the value of peer support among adolescents, which could help reduce the burden of psychosocial care on caregivers and healthcare workers.